2022
DOI: 10.1111/jocn.16300
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the 24/7 nurse practitioner model on emergency department stay at a level 1 trauma center: A retrospective study

Abstract: Aims The aim of the study was to assess the impact of 24/7 trauma nurse practitioner service model on the emergency department patient flow. Background Seamless transition of trauma patients through the emergency department to inpatient hospital care is crucial for coordination of care, clinical safety and positive health outcomes. A level 1 trauma centre located in Southern West Virginia, USA expanded their trauma nurse practitioner service covering the emergency department 24/7. Design Retrospective cohort s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Beyond routine institutional reviews of ENP practice, the literature demonstrates collective evidence of quality and safe care provided by ENPs. Similar to the successes experienced by the inclusion of NPs among inpatient hospital services (Aiken et al, 2021; Hardway et al, 2022), the benefits of NPs within emergency care teams have been repeatedly demonstrated in the literature for decades (Carter & Chochinov, 2007; Fowler et al, 2019; Powers et al, 1984). Multiple US studies have reported positive outcomes of emergency care delivered by NPs.…”
Section: Outcomes Of Nurse Practitioner Care In Emergency Settingsmentioning
confidence: 78%
“…Beyond routine institutional reviews of ENP practice, the literature demonstrates collective evidence of quality and safe care provided by ENPs. Similar to the successes experienced by the inclusion of NPs among inpatient hospital services (Aiken et al, 2021; Hardway et al, 2022), the benefits of NPs within emergency care teams have been repeatedly demonstrated in the literature for decades (Carter & Chochinov, 2007; Fowler et al, 2019; Powers et al, 1984). Multiple US studies have reported positive outcomes of emergency care delivered by NPs.…”
Section: Outcomes Of Nurse Practitioner Care In Emergency Settingsmentioning
confidence: 78%